2020
DOI: 10.1177/1129729820968400
|View full text |Cite
|
Sign up to set email alerts
|

The patient experience of hemodialysis vascular access decision-making

Abstract: Background: To describe vascular access (VA)-related decision-making from the patient perspective, in patients who have already chosen hemodialysis as their renal replacement modality, and identify areas where physicians can improve this experience. Methods: In-person, semi-structured interviews with 15 patients with end-stage kidney disease were systematically analyzed by two independent researchers using thematic analysis. Interviews were conducted until systematic analysis revealed no new themes. Results: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…In 1 qualitative study, the majority of patients interviewed (14 of 15) disclosed minimal engagement in vascular access decision making and lack of a clear understanding about the different types of access and their consequences. 24 In an interview of 10 older adults enrolled in a pilot clinical trial of AVF versus AVG vascular access strategy 25 and interviewed 6 months after AV access placement, all (10 of 10) patients perceived the intervention of AV access placement as "something that needed to be done"; 6 (of 10) patients declared that the decision of AV access placement was made collaboratively between the treating physician, patient, and/or family members. When asked to reflect on each access (catheter vs. AV access received) and compare accessrelated experiences, most patients (7 of 10) reported a preference for catheter rather than AV access; reasons for catheter preference were AV access failure (n ¼ 3) and dislike of needles (n ¼ 4).…”
Section: The Current State Of Hemodialysis Vascular Access Practicementioning
confidence: 99%
See 2 more Smart Citations
“…In 1 qualitative study, the majority of patients interviewed (14 of 15) disclosed minimal engagement in vascular access decision making and lack of a clear understanding about the different types of access and their consequences. 24 In an interview of 10 older adults enrolled in a pilot clinical trial of AVF versus AVG vascular access strategy 25 and interviewed 6 months after AV access placement, all (10 of 10) patients perceived the intervention of AV access placement as "something that needed to be done"; 6 (of 10) patients declared that the decision of AV access placement was made collaboratively between the treating physician, patient, and/or family members. When asked to reflect on each access (catheter vs. AV access received) and compare accessrelated experiences, most patients (7 of 10) reported a preference for catheter rather than AV access; reasons for catheter preference were AV access failure (n ¼ 3) and dislike of needles (n ¼ 4).…”
Section: The Current State Of Hemodialysis Vascular Access Practicementioning
confidence: 99%
“…Other studies revealed that patients perceive vascular access decisions as "intertwined and interrelated" with dialysis initiation and tend to not differentiate between dialysis and vascular access in decision-making, 22 all of which deprive the patients from meaningful engagement in vascular access decision making. 24…”
Section: The Current State Of Hemodialysis Vascular Access Practicementioning
confidence: 99%
See 1 more Smart Citation
“…These studies revealed themes of heightened vulnerability, device intrusiveness on the body, disfigurement, mechanization of the body, impinging on way of life, imposing burdens, self-preservation and ownership, and confronting decisions and consequences 65,66 . In-person semi-structured interviews have probed patient reports on vascular access decision making and outcomes attitudes 58,67 . In one qualitative study, the majority of patients interviewed (14 of 15) disclosed minimal engagement in vascular access decision making and accepted vascular access recommendations from physicians.…”
Section: Patients' Values and Preferences For Vascular Access Carementioning
confidence: 99%
“…21,22 Other work characterizing patients' perspectives on vascular access has suggested that the emotional and physical tolls of living with their access are high 23 and that factors such as communication quality, information seeking, and supportive relationships underlie their decisions. 24 However, an understanding of how the perspectives of patients and others involved in the circle of care contribute to shared decision making in this context is limited.…”
mentioning
confidence: 99%